2010
DOI: 10.1021/bi9021022
|View full text |Cite
|
Sign up to set email alerts
|

Complement Protein C1q Recognizes Enzymatically Modified Low-Density Lipoprotein through Unesterified Fatty Acids Generated by Cholesterol Esterase

Abstract: We previously reported that enzymatically modified low-density lipoprotein (E-LDL) particles obtained by LDL treatment with trypsin and then cholesterol esterase are recognized by C1q and activate the C1 complex of complement. The objective of this study was to identify the E-LDL component(s) recognized by C1q. In addition to trypsin, plasmin, thrombin, tryptase, and matrix metalloprotease-2 each yielded E-LDL particles with high C1-activating efficiency, and the C1 activation extent was strictly dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…The analysis of the lipid composition of early valvular cusp lesions (grade 1) compared with internal control tissues by mass spectrometry detecting both unesterified cholesterol and linoleic acid corroborated our immunohistochemical findings. While it is known that free cholesterol has an intrinsic complement‐activating capacity (see later),28 free fatty acids contained in the eLDL particle not only bind and activate C129 but also play multifaceted roles through their dual capacity to exert stimulatory and cytotoxic effects on neighboring cells 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the lipid composition of early valvular cusp lesions (grade 1) compared with internal control tissues by mass spectrometry detecting both unesterified cholesterol and linoleic acid corroborated our immunohistochemical findings. While it is known that free cholesterol has an intrinsic complement‐activating capacity (see later),28 free fatty acids contained in the eLDL particle not only bind and activate C129 but also play multifaceted roles through their dual capacity to exert stimulatory and cytotoxic effects on neighboring cells 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…C1q is also activated by enzymatically modified LDL containing free fatty acids together with phospholipid (151). C1q enhanced the uptake of oxLDL into macrophages with subsequent activation of the cells including increased CD80, PECAM1, and MCP-1 release but also induction of ABCA1 and ABCG1 with enhanced cholesterol efflux to HDL (543).…”
Section: The Complement Pathway and Atherogenesismentioning
confidence: 99%
“…Besides its role in the activation of the classical complement pathway in response to pathogen infection, C1q plays a crucial role in the detection and scavenging of a wide variety of noxious alteredself substances, such as β-amyloid fibrils, the pathological form of the prion protein, apoptotic and necrotic cells, or modified forms of the lowdensity lipoprotein. [5][6][7][8][9][10][11] Interestingly, unlike the other complement proteins, C1q is produced by macrophages and immature dendritic cells. Numerous studies have shown that C1q influences the phagocyte "status" through regulation of cytokine expression 12,13 and that it may be involved in the nonimmunogenic presentation of self-antigens through its ability to modulate maturation of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%